Cash Waqf Linked Sukuk: Potential and Challenges - Fusthathul Nur Sasongko; Tika Widi Astuti; Muhammad Syaukin Muttaqin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
Waqf as an instrument of Islamic economics in the modern era as it is today. Indonesia with the most Muslims in the world has a very large potential for waqf, with a nominal potential of approximately Rp. 2,000 Trillion and it would be a shame if that great potential could not be optimized as well as possible. Then CWLS is expected as an alternative instrument for optimizing the potential of waqf and examining the obstacles that will be faced . The purpose of this research is Cash Waqf Linked Sukuk as an instrument for optimizing the potential of waqf in Indonesia. CWLS is a productive cash waqf which is expected to improve the national economy. The research method used is library research where by reviewing all articles, books, and writings of experts to strengthen CWLS, you can maximize the potential of waqf in Indonesia. The results obtained are that CWLS is able to be an alternative for optimizing the potential of waqf, then the obstacles faced are the level of literacy as community insight in doing waqf and the level of religiosity of the community in doing waqf.